2006
DOI: 10.1634/stemcells.2005-0224
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Characteristics and In Vivo Immunosuppressive Activity of Compact Bone-Derived Murine Mesenchymal Progenitor Cells

Abstract: In contrast to the considerable amount of data that documents the biological properties of mesenchymal progenitor cells from human and other species, there is still paucity of information about mouse counterparts, as their purification and culture expansion procedures remain rudimentary. In the present study, murine mesenchymal progenitor cell (muMPC) culture was developed by explant culture of collagenase-digested bone fragments after removal of the released cells. During cultivation, fibroblastoid cells spro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 51 publications
7
67
0
2
Order By: Relevance
“…Because SDF-1 is reportedly regulated by a hypoxia-specific transcriptional factor, hypoxia-inducible factor 1, the expression of SDF-1 may increase rapidly after the blood supply is stopped in those models (25). However, any trophic vasculature was not apparently affected in our live bone graft model (33). Furthermore, it can be expected that infiltration from the neighboring bone marrow retains the blood supply to the graft bone to some extent.…”
Section: Discussionmentioning
confidence: 84%
“…Because SDF-1 is reportedly regulated by a hypoxia-specific transcriptional factor, hypoxia-inducible factor 1, the expression of SDF-1 may increase rapidly after the blood supply is stopped in those models (25). However, any trophic vasculature was not apparently affected in our live bone graft model (33). Furthermore, it can be expected that infiltration from the neighboring bone marrow retains the blood supply to the graft bone to some extent.…”
Section: Discussionmentioning
confidence: 84%
“…4A). Mature macrophages were also observed in bone explant cultures (data not shown), another common means of obtaining human and rodent primary osteoblasts (23,24). Immunocytochemical analysis was used to locate TNF and showed that F4/80 ϩ mature macrophages are the cellular source of TNF within these cultures (data not shown).…”
Section: Macrophages Are the Lps-responsive Cell Within Primary Osteomentioning
confidence: 94%
“…Then the chips were incubated in 1 mg/ml of type II collagenase (Sigma-Aldrich) at 37 C for 2 hr with shaking. After wash with a-MEM for three times, bone fragments were cultured in a-MEM containing 10% selected FBS at 37 C in 5% CO 2 for cell expansion (Guo et al, 2006).…”
Section: Isolation and Expansion Of Mscs From Compact Bonementioning
confidence: 99%